2015
DOI: 10.1159/000430803
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Bethesda System for Reporting Thyroid Cytopathology in the Eastern Province of Saudi Arabia: A Follow-Up Study

Abstract: This is a follow-up study to our previous analysis of thyroid aspirates utilizing the Bethesda System for Reporting Thyroid Cytology (BSRTC). The same study design was utilized for 2 years comparing 2 periods. A total of 251 thyroid aspirates from 218 patients were reviewed and deemed comparable to the previous cohort. The variance and consequently the number of interpretations dropped from 26 to 11 with a statistically significant 58% reduction and more consistency. Our unsatisfactory rate dropped from 22 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…15 This was followed up by another study showing the impact of the initial campaign and its impact on the major key performance indicators. 16 As evidenced by the results of our second follow-up study, the awareness and acceptance of TBSRTC has dramatically increased with statistically significant improvement and demonstrable changes. 16…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…15 This was followed up by another study showing the impact of the initial campaign and its impact on the major key performance indicators. 16 As evidenced by the results of our second follow-up study, the awareness and acceptance of TBSRTC has dramatically increased with statistically significant improvement and demonstrable changes. 16…”
Section: Introductionmentioning
confidence: 72%
“…16 As evidenced by the results of our second follow-up study, the awareness and acceptance of TBSRTC has dramatically increased with statistically significant improvement and demonstrable changes. 16…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…An evaluation of the Bethesda system with regard to its contribution to establishing a common terminology demonstrated that diagnostic controversies among pathologists had dwindled to 11% compared to more than a quarter of cases. Furthermore, the rates of nondiagnostic or unsatisfactory reports had been almost halved [13].…”
Section: Discussionmentioning
confidence: 99%